Haplotypes of the steroid 21-hydroxylase gene region encoding mild steroid 21-hydroxylase deficiency. - Haglund-Stengler, B (1991)
Haplotypes of the complement 4 (C4) and steroid 21-hydroxylase [21-OHase; steroid hydrogen-donor: oxygen oxidoreductase (21-hydroxylating), EC 1.14.99.10] repeated gene complex were studied in nine families with at least one member affected with a mild form of 21-OHase deficiency. DNA probes from different parts of the repeated C4/21-OHase unit were used to follow the segregation of hybridization patterns in the families. Ten structurally distinct haplotypes of the C4/21-OHase gene region were identified, and the encoded phenotype was assigned to 34 of the 36 C4/21-OHase haplotypes. Four structurally different haplotypes with three C4/21-OHase repeat units were found. Eight of the nine haplotypes found with triplications of the C4/21-OHase repeat unit encoded the mild form of 21-OHase deficiency, whereas one particular triplicated haplotype encoded a severe form of the disease. In one case the mild form of 21-OHase deficiency was encoded by a haplotype with a single C4/21-OHase repeat unit. Mild 21-OHase deficiency was predicted in a patient by the presence of a triplicated haplotype. The finding of deranged 21-OHase genes on all triplicated C4/21-OHase haplotypes indicate that most of these common haplotypes carry mutated 21-OHase genes, and thus may cause functional polymorphism of general importance in the population.